What Does 'Collaboration' Without Government Look Like? The Network Qualities of an Emerging Partnership. Issue 3 (26th April 2016) - Moran, Michael; Joyce, Andrew; Barraket, Josephine; MacKenzie, Caitlyn; Foenander, Emily
Abstract : Cross‐sectoral partnerships are increasingly common in Australian human service delivery. Yet research has not often focused on partnerships where private actors broker an arrangement to address complex community needs. Using a combination of interviews, focus groups, and social network analysis (SNA), this paper investigates the network qualities of a nascent partnership between a not for profit (NFP) service provider and a major retail water company that seeks to address financial hardship. Ultimately, we assess whether this represents genuine collaboration or another form of joint action. We find that the privately steered partnership generates instrumental benefits characteristic of cross‐sectoral arrangements, as well as challenges. SNA reveals a very high degree of connection between the partner organisations, but the results suggest that the partnership is coordinative rather than collaborative. We also find that this is leading to tacit organisational and institutional modifications as the NFP assumes a 'market facing' posture and adjusts to the demands of working with private sector partners. However, at this early stage of development, the level of systemic adjustment between both organisations remains incomplete. Abstract : This article examines a partnership brokered by a private actor to address community needs in the area financial hardship. Using interviews and network analysis we examine the network qualities of the partnership. We find that it is leading to tacit organisational modifications but systemic adjustment between partners remains incomplete.